Maxillofacial Prosthesis: A Review of Treatment Concepts for Better Prosthesis Prognosis - Sanjay Prasad (Bengal Journal of Otolaryngology and Head Neck Surgery, 2017)
Maxillofacial prosthesis currently finds itself experiencing more change than at any other time over past 50 years of its recognized existence. Rehabilitation of facial defect, either congenital or acquired, is a difficult challenge for the surgeon as well as prosthodontist. The prosthodontist is limited by the properties of the materials available for facial restorations, the mobility of soft tissue surrounding the defects, the difficulty of establishing retention for large prosthesis, and the patient ability to accept the outcome. However, the acceptance of prosthesis recently has improved remarkably due to better coordination between surgeon and prosthodontist and introduction of dental implant which has dramatically improved the retention and esthetic that result from accurate and repeatable positioning of the implant, and the ease of maintenance.  Dramatic improvement in the acceptance of prosthesis is seen if the prosthodontist participation can begin early in the course of patient care which ultimately will increase the quality of life (QoL) of the patient.